Mordenite-Type Zeolite from Iraq Sand: Synthesis and Characterization - ahmed, Abdulla M.; Jarullah, Aysar T.; Hussein, Hala M.; Ahmed, A. N. (Journal of Petroleum Research and Studies, 2023)
Mordenite's excellent physical and chemical qualities set it apart from other zeolites with similar applications in industry. Mordenite is frequently produced through hydrothermal processing with TEA+ cations. The best template agent is TEA+ cations, despite the fact that they may lead to a variety of problems, such as the release of toxicity, the high cost of production, the contamination of wastewater, and environmental damage. So, it's important to develop a mordenite synthesis technique that doesn't need an organic template or a cheap template. The mordenite-type zeolites were prepared using sand from the western part of Iraq (Ar-Rutbah). Silica was extracted from Iraqi sand as a silica source and sodium aluminate as a source of alumina Al by using the SOL-GEL method through the hydrothermal technique at temperatures ranging from 23 to 27 °C over a period of 7 days. Analyses such as XRD, BET surface area AFM, FT-IR, and FE-SEM were performed on the sample. The average particle size was 31.9 nm, and the BET surface area was 202.487. XRF detected the ratio of silica to alumina (Si/Al = 4.55), and the exchange of sodium ions for hydrogen ions through ionic exchange is 100%. The micrograph clearly reveals a tiny portion of the crystal band with a flaky habit, while FE-SEM images of synthesized H-MOR show that plates form the majority of the crystals.